An FFT-based vibration characterization on road profile of two-wheeler electric vehicle - Firmansyah, Mohamad Ardy; Feriyanto, Dafit; Firdaus, Himma; Pranoto, Hadi; Istiqomah, Istiqomah (Universitas Mercu Buana, 2025)
Vibration is an inevitable physical phenomenon; excessive and uncontrolled amounts of vibration can result in damage and system failure. In accordance with various automotive product certification standards, vehicle batteries or rechargeable electrical energy stotrage system (REESS) must undergo a vibration test to assess their mechanical integrity. This study aims to broaden the perspective on vibration assessment by examining it during vehicle operation and assessing the protective capabilities of vehicle suspension against vibrations from damaged roads in two-wheeled electric motor vehicles. The proposed method involves installing an accelerometer on the battery pack body placed in the battery compartment. The experimental setup involved conducting tests on a 125-meter track, with the vehicle traversing roads characterized by concrete cracks, uneven surfaces, and potholes. Two distinct speed variations were selected for analysis: 10 and 15 kilometers per hour. The results obtained from the Rion VA 12 portable vibration analyzer are presented as a plot of the fast Fourier transform (FFT) graph. The maximum acceleration recorded was 2.35 and 1.98 G at the same frequency of 7 hertz (Hz). This research method and result aligns with others, including those focused on assessing road damage, passenger comfort, and vehicle component damage, such as shock absorbers. In the future, the development of a vehicle battery support structure is anticipated to further minimize vibration disturbance by reducing the peak acceleration values depicted in the FFT graph. The minimization of incoming vibrations is expected to enhance the safety and durability of the battery pack.